1976
DOI: 10.1042/bj1530423
|View full text |Cite
|
Sign up to set email alerts
|

The association of yeast phosphoglycerate kinase (EC 2.7.2.3)

Abstract: 1. A mol.wt. of 40030 +/- 830 has been estimated for phosphoglycerate kinase in concentrations less than 0.1 g/100 cm3 comparing favourably with expected values from X-ray diffraction measurements by 10% lower than the previously reported molecular weights made at higher concentrations. 2. The so20w, was estimated to be 3.12(+/-0.02)x10(-13)s and the coefficient had a low concentration dependency giving a g value (concentration-dependency) of 2.3 +/- 1.6cm3 .g-1. This agrees with previous qualitative observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1977
1977
1991
1991

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…There is abundant evidence that the enzyme exists as a monomer at the assay concentrations [9], so negative co-operativity between subunits would be impossible. The affinity-elution chromatographic experiment, together with other evidence of homogeneity, appears to rule out two non-interconvertible forms of the enzyme with different affinities for the substrates (the detailed nature of the kinetic plots is also not consistent with this idea).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is abundant evidence that the enzyme exists as a monomer at the assay concentrations [9], so negative co-operativity between subunits would be impossible. The affinity-elution chromatographic experiment, together with other evidence of homogeneity, appears to rule out two non-interconvertible forms of the enzyme with different affinities for the substrates (the detailed nature of the kinetic plots is also not consistent with this idea).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, many workers reported biphasic double-reciprocal or Hofstee-Eadie plots, and suggested that these indicated two K,,, values for separate reactive sites, or were due to complex interactions involving magnesium ions [3,7,8]. However, there is no doubt that the enzyme is monomeric at low concentrations [9], and crystallographic studies suggest that both the yeast and the horse-muscle enzyme possess only one tight binding site for adenine nucleotides [lo, 111. Curved or biphasic plots could be made more linear by alterations of magnesium ion concentrations, or changing the buffers [3], but this did not explain the anomalies.…”
mentioning
confidence: 99%
“…The concentrations of solutions of phosphoglycerate kinase (wild-type and mutant) were determined spectrometrically by using an AI mg'm' value of 0.49 (Spragg et al, 1976).…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…UB6 9BH,U.K. ) to control the scanner and to average transmissions at each radius from up to nine individual sectors (the system is fully described in Spragg et al, 1976). Between three and six scans of each solution were collected and analysed individually.…”
Section: Equilibrium Experimentsmentioning
confidence: 99%
“…A further error arises from uncertainties in the radial dimensions, amounting to approx. 40Opm (Spragg et al, 1976), produced by erroneous location of the two reference slits and giving a systematic error in any scan. It is thought that this accounts for the displacement of the fitted curve for combined scans compared with records from one scan within the combination (Fig.…”
Section: M1wl+4mll 4w4mentioning
confidence: 99%